전산유체해석(CFD) 모의를 이용한 다공형 스크류 노즐 입수관이 적용된 물탱크 내부의 사류구역 최소화에 대한 유동특성 - 송준혁(Jun Hyuck Song); 권종우(Jong Woo Kwon); 최종웅(Jong Woong Choi); 왕창근(Chang Keun Wang) (Daehan hwan'gyeong gonghag hoeji, 2015)
This study was carried out for the purpose of minimizing the area of rapid flow inside the water tank. And the shape of incurrent canal was improved, and then the characteristics of fluid flow occurring inside the water tank was analyzed by using the Computational Fluid Dynamics (CFD) simulation method. better multiple hoe screw nozzle incurrent canal was used instead of conventional drop current canal used for the water tank. And according to the results of analyzing the characteristics of fluid flow, in case a screw blade was installed inside the nozzle, fluid flow was sprayed wide. And wide fluid flow was shown inside the cylindrical water tank too. Besides, a tracer simulation was carried out, in case of installing 1 and 2 multiple hoe screw nozzle incurrent canals at the cubic water tank. As a result, MODAL, MODAL index value was close to 1, in case of installing 2 canals. Therefore, it was possible to obtain the results of being close to the characteristics of plug flow. 본 연구는 물탱크 내부의 사류구역 최소화에 목적을 두고 진행하였으며 입수관의 형태를 개선하여 물탱크 내부에서 발생하는 유동특성을 전산유체역학(Computational Fluid Dynamics, CFD)모사 기법을 이용하여 분석 하였다. 기존에 물탱크에 사용되던 자유낙하 방식의 입수관을 다공형 스크류 노즐 입수관으로 개선하고 유동 특성을 분석한 결과 노즐 안에 스크류 날개가 설치된 경우 유동흐름의 폭이 넓게 분사 되었으며 원통형 물탱크 내부에서도 넓은 유동 흐름이 나타났다. 또한 사각형 물탱크에 다공형 스크류 노즐 입수관이 1개 설치되어 있을 경우와 2개 설치되어있을 경우의 유동해석과 추적자모의를 수행하였으며 그 결과 입수관을 2개 설치할 경우 MODAL, MORILL index값이 1에 가깝게 나타나 Plug Flow 특성에 근접하단 결과를 얻을 수 있었다.